TINGKAT PARTISIPASI MASYARAKAT TERHADAP KEPEMILIKAN AKTA TANAH (Studi Di Desa Bale Kecamatan Bukit Kabupaten Bener Meriah Provinsi Aceh) - Vera, Zefri Noci (Universitas Medan Area, 2016)
Community participation is needed of the ownership of land, current land position in accordance with the development, the land is a means to carry out the construction, agricultural land, industry, and trade. The problems proposed in this research is